2015 Rosalie Wolf Memorial Award Lecture: Past, present, and future of elder abuse. Issue 4 (19th October 2016) - Dong, XinQi; Wang, Bei
ABSTRACT: This article aims to advance the global issue of elder abuse through exploring how the current body of elder abuse literature can collectively pave the way for present and future directions for research, practice, and policy.